Economic-Legal Aspects of Hotel Service Provision - NIKOLSKAYA, Elena Yurievna; USPENSKAYA, Marina Evgenjevna; LYSOIVANENKO, Elena Nikolaevna; MELTSOV, Alexey Viktorovich; KRAMAROVA, Tatyana Yuryevna (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).02, 2019)
This paper seeks to provide an analysis of the key economic-legal aspects of hotel service provision in present-day conditions. It is established that currently there are at least three steps that could be taken to enhance the provision of hotel services: (1) holding parliamentary hearings on the development of the tourism and hotel sectors with participation from relevant specialists; (2) introducing uniform rules for hotel classification based on the rules developed by UNWTO and establishing hotel categories based on Hotelstars Union, a hotel rating system developed by the HOTREC; (3) designating an agency that will issue hotel categorization certificates and will operate within the framework of government authorities. It is proven that the quality of hotel services must be in keeping with the terms of the hotel services agreement. However, the issue of responsibility in the area of provision of hotel services is complicated by the existence of numerous laws and regulations providing for this type of responsibility.